The economics of measuring quality of life by the standard gamble method - EISENSTAT, Eric; EPURE, Manuela; GRAY, Patrick Francis (Annals of Spiru Haret University. Economic Series, 2011)
Of the countless methods for measuring the quality of life (QOL) that have been proposed and analyzed by the vast, multi-disciplinary literature over the past decades, only a select few are alluded to in Romanian scientific circles, and even fewer are actually implemented in practical applications. In adapting existing techniques and engineering a viable measurement system specific to Romania, there exists an important opportunity to re-evaluate the merits and shortcomings of established approaches. As a specific example, we consider the Standard Gamble (SG) method of eliciting “subjective utilities” related to particular health states. The re-evaluation is accomplished from three perspectives: theoretic consistency, interpretability and practicality. It is demonstrated that consistent with economic theory, the appropriate interpretation of SG derived measures is that of a Hicksian change in welfare valuation, rather than a cardinal measure of preferences. A practical consequence of the latter is that SG will necessarily produce a higher QOL value for individuals exhibiting more risk aversion. This leads us to contemplate that in fact SG may be a more appropriate methodology in other contexts, not necessarily health-related, where quality of life may indeed be correlated with the willingness to take risks.